Differentially gene expression profiling reveals effect similarities of everolimus, asiaticoside, and asiatic acid on TSC-derived renal angiomyolipoma - Ninie Nadia Zulkipli, Idris Long, Habibah A. Wahab, Teguh Haryo Sasongko, Nur Atiqah Azhar, Rahimah Zakaria (Journal of Applied Pharmaceutical Science, 2024)
Tuberous sclerosis complex (TSC) is a rare genetic disorder characterized by the development of benign hamartomas in various organs, including renal angiomyolipoma. The current medical standard treatment for TSC-associated renal angiomyolipoma involves the use of a mammalian target of rapamycin (mTOR) inhibitor. To better understand the molecular basis of this treatment approach, our study aimed to identify differentially expressed genes (DEGs) in the UMB1949 cell line following treatment with asiaticoside and asiatic acid and compared them to the effects of everolimus treatment. Using the RT2 Profiler polymerase chain reaction (PCR) array panel, we systematically analyzed the expression patterns of these DEGs, utilizing gene ontology (GO) terms and Kyoto encyclopedia of genes and genomes (KEGGs) pathway analyses to elucidate the underlying mTOR inhibitory mechanisms in UMB1949. Our results revealed that all three substances shared five DEGs (four upregulated: CAB39, PRKCE, RRAGC, RPS6KA5, and one downregulated: DEPTOR), as well as seven common GO terms and KEGG pathways, suggesting that the inhibitory activity against mTOR closely mirrors that of everolimus. Moreover, we identified a significant overlap in DEGs involved in cell inhibition via the mTOR pathway across all treated groups. Based on the comprehensive analysis of DEG bioinformatics data, we hypothesized that asiaticoside and asiatic acid exhibit functions comparable to everolimus, with asiaticoside displaying a closer similarity to everolimus than asiatic acid. These findings provide valuable insights into the molecular mechanisms and potential mTOR inhibitors for TSC-associated renal angiomyolipoma and establish a crucial link between our study and the current therapeutic landscape of TSC.
Keywords: Tuberous sclerosis complex, mTOR inhibitors, differentially expressed genes, asiaticoside, asiatic acid, everolimus